PERANCANGAN STANDAR KUALITAS PELAYANAN PADA PT INDOCARE PACIFIC BATAM - sihombing, indah mentari prisna; Fajrah, Nofriani (Computer Science and Industrial Engineering, 2022)
Service quality is an action or deed that is carried out in accordance with the wishes of the user in order for the user to feel satisfied with the action or deed taken. If the user feels it is not in accordance with the user's wishes, there will be a user complaint against the company. There are complaints from PT Indocare Pacific users caused by malfunctions of the products provided by PT Indocare Pacific. The handling and response time for user complaints from the company takes quite a long time. This research was conducted with the aim of designing service quality standards at PT Indocare Pacific Batam to be able to improve the quality of users so as to achieve service user satisfaction. The method used is Plan, Do, Check, Action (PDCA), SixSigma, and Standard Operating Procedure (SOP) as a proposed improvement for the company. The results of this study of the 5 dimensions of servqual that have been carried out data processing with DPMO and sigma calculations obtained each servqual dimension obtains a sigma value which shows the company needs to make improvements and improve service quality through improvement of service procedures in the form of SOP.